PEMANFAATAN INSTAGRAM IVAN LANIN SEBAGAI SUMBER PEMBELAJARAN BAHASA INDONESIA SMP - Muhaimini, Maryam Sri; Rahmawati, Laili Etika (Universitas Hamzanwadi, 2022)
This research was conducted to analyze the Indonesian spelling and conjunctions contained on Ivan Lanin's Instagram social media account which will later be used as learning resources for seventh grade junior high school students. This research is a research using descriptive method. The data source of this study was obtained from Ivan Lanin's Instagram social media account in the form of Indonesian spelling and conjunctions. Data collection techniques used listening and note-taking techniques. The data validation technique uses data triangulation. Data analysis shows that social media accounts, especially Instagram, have benefits as learning resources that can be applied in learning or in teaching and learning activities. Forms of using Instagram social media accounts as learning resources include supporting learning activities, the internet as a source of information. The results showed that there was an explanation of the Indonesian spelling and conjunctions contained in Ivan Lanin's Instagram account. The types of spelling found on Ivan Lanin's Instagram are the use of letters, writing words, and the use of punctuation. The spelling on Ivan Lanin's Instagram is in line with the material for personal letters and official letters in KD 4.12. In addition, there is an explanation of conjunctions on Ivan Lanin's Instagram account which can then be a source of learning on narrative text material in KD 4.4.Keywords: Social Media, Instagram, Spelling, Conjunction